English Lexical Borrowing in The April 2023 Editorials of Kompas: A Discourse Analysis - Rifa Suci Wulandari; Nihaya Nur Fadila; Nur Aini Syah (Social Science Academic, 2025)
The increasing use of English terms in Indonesian-language newspapers reflects the influence of globalization on media discourse. While previous studies have discussed code-mixing and lexical borrowing in mass media, few have specifically examined the systematic use of English terms in editorial columns, which are influential in shaping public opinion. Addressing this gap, this study investigates the use of English terms in the editorial column of the Kompas daily newspaper, focusing on the April 2023 edition. The data were drawn from Indonesian-language editorials published in Kompas and analyzed using qualitative discourse analysis. The results indicate that English terms in Kompas editorials are most common in politics, law, and governance (29.9%), followed by economy and development (22.4%) and society and culture (19.4%). These terms are mainly used to express formal and contemporary issues. Verbs account for only 4.4% of the data, indicating that English borrowing is largely limited to content words, especially nouns. Overall, English influence in the editorials is primarily lexical and does not affect Indonesian grammatical structure. This study contributes to sociolinguistic and media discourse research by providing empirical evidence on the grammatical distribution of English terms in Indonesian editorials and highlighting their functional role in written journalistic discourse.